2018
DOI: 10.1021/acs.jpcc.7b11249
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Lithiation of Ge: New Insights by Operando Spectroscopy and Diffraction

Abstract: The relatively high cost of metallic germanium (Ge) as a lithiumion battery negative electrode material is more than counterbalanced by its high capacity, high lithium diffusivity, and electronic conductivity. Using a unique and highly complementary set of operando characterization techniques, we propose a complete mechanism for the reversible lithiation of Ge. The electrochemical mechanism is found to be determined by the process of discharge/charge: (i) independent of the charge/discharge rate amorphous a-Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Secondly, recent studies indicate that Ge is particularly sensitive to the cycling conditions and parameters such as C/rate, morphology or electrode formulation can influence the type of phases that are formed. For instance in one of our previous studies for the lithiation of Ge, it was found that the cycling at relatively slow regime permits the stabilization of Li 17 Ge 4 , a more lithiated phase than Li 15 Ge 4 . Another study concerning the sodiation of Ge Nanowires, has shown the formation of Na 1.6 Ge, much sodiated phase than the expected NaGe .…”
Section: Resultsmentioning
confidence: 93%
“…Secondly, recent studies indicate that Ge is particularly sensitive to the cycling conditions and parameters such as C/rate, morphology or electrode formulation can influence the type of phases that are formed. For instance in one of our previous studies for the lithiation of Ge, it was found that the cycling at relatively slow regime permits the stabilization of Li 17 Ge 4 , a more lithiated phase than Li 15 Ge 4 . Another study concerning the sodiation of Ge Nanowires, has shown the formation of Na 1.6 Ge, much sodiated phase than the expected NaGe .…”
Section: Resultsmentioning
confidence: 93%
“…Equations (3) and( 4) assume that SiAs or GeAs is converted into the highest reported Li-Si(Ge) binaryp hase and the most commonly accepted form of lithium arsenide. [43][44][45][46][47][48][49][50] GeAs þ x Li ! Li x GeAs ð182 x mAh g À1 Þ ð1Þ…”
Section: Resultsmentioning
confidence: 99%
“…Full delithiation was enforced by holding the potential at 3 V at the end of charge. The whole data set consisting of 126 Co K‐edge XAS spectra was treated globally using the chemometric approach already described in our previous studies . In short, the number of independent components needed to describe the whole set of spectra is first obtained by PCA, and in a second step the corresponding pure spectral components are reconstructed by MCR‐ALS algorithm by imposing physical and chemical constraints .…”
Section: Resultsmentioning
confidence: 99%